Effective Ways and Approaches of Using New Pedagogical Technologies in Higher Education (In the Example of Teaching Foreign Languages) - Abdullaeva Munojot Mukhtorovna (Genius Journals, 2024)
This study investigated the rapid growth of technology has brought many innovations in education and especially in language teaching. In order to offer and create successful classes language teachers, especially English language teachers are using different tools facilitate the teaching process and make it more useful and efficient, besides textbooks and other interesting and engaging activities, which ensure student centeredness, autonomy, interaction and connectivity to a certain theme, such as computer-assisted language learning (CALL),"social computing" Digital Video on Demand are widely used in EFL classrooms. This paper first attempts to explore the goals of using educational technologies in the teaching process and the advantages of using materials in EFL teaching, on the basis of which proposes a framework of teaching principles, strategies and specific tips which facilitate EFL teaching. Then will bring theories and practice related to the use of technologies in language learning especially in ESP classes at a university level and the reason why modern educational technologies can be considered as valuable pedagogical tools, to facilitate the teaching process and learning process at all
Keywords: technology; CALL; social computing; Class Web Site